Chances of Effective Urban Policy in Hungary under the Influence of the European Cohesion Policy - Edit Somlyódyné Pfeil (DETUROPE)
The goal of the paper is to search for the state environmental conditions for an effective urban governance by the analysis of the Hungarian processes of the last six years. The survey is focused, on the one hand, on Hungarian towns considered as small and medium-sized towns by European scales; on the other hand, the conditions for the birth of co-operations between these towns and their regions, and among the different sectors are also emphasised. This is the viewpoint from which the paper tries to grab the content and tools of Hungarian urban policy, and the special features of this policy. It is also crucial in this respect how the reform programme of public administration influences governance chances of cities both as regards the location of tasks and the organisational system; and also how much the cohesion policy of the EU and its urban dimension affects the public policy processes.